Analisis Kelayakan Pemasangan Load Break Switch Motorized Pada Penyulang Anoa Di PT. PLN (Persero) ULP Rumbai - Prawira, Ganda; Situmeang, Usaha; -, Monice (Teknik Elektro Universitas Lancang Kuning, 2025)
Disturbances in the distribution system cause energy losses and reduce the quality of electricity services. This study aims to analyze the feasibility of installing a Motorized Load Break Switch (LBS) to improve the reliability of the distribution system on the Anoa Feeder at PT PLN (Persero) ULP Rumbai. The method used in this study is simulation using ETAP software to compare the reliability indices of SAIDI, SAIFI, and ENS before and after the installation of the Motorized LBS. The results show that after the installation of the LBS, there was a decrease in SAIDI by 73%, SAIFI by 89%, and ENS by 70%, resulting in a reduction of financial losses from IDR 88,438,619 to IDR 25,920,330 per year. In conclusion, the installation of the Motorized LBS is feasible to implement to improve the reliability of the distribution system and reduce losses due to power outages.